2016
DOI: 10.1148/rg.2016150198
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric CT Imaging: Challenges and Solutions

Abstract: The obesity epidemic in the adult and pediatric populations affects all aspects of health care, including diagnostic imaging. With the increasing prevalence of obese and morbidly obese patients, bariatric computed tomographic (CT) imaging is becoming common in day-to-day radiology practice, and a basic understanding of the unique problems that bariatric patients pose to the imaging community is crucial in any setting. Because larger patients may not fit into conventional scanners, having a CT scanner with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Obesity was noted to be a cause of non-diagnostic CTPA examinations in several studies, and the increasing prevalence of obesity may play a role in the worsening diagnostic yield of CTPA. 6 CTPA studies on overweight and obese patients show statistically significantly decreased levels of pulmonary artery enhancement, signal-tonoise ratio (SNR), contrast-to-noise (CNR) and subjective image quality 6,42 (Figure 2). In a retrospective study in 2016, Yeo et al found that 6% of 403 total CTPAs were indeterminate, with 23 suboptimal examinations, and 1 non-diagnostic examination.…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity was noted to be a cause of non-diagnostic CTPA examinations in several studies, and the increasing prevalence of obesity may play a role in the worsening diagnostic yield of CTPA. 6 CTPA studies on overweight and obese patients show statistically significantly decreased levels of pulmonary artery enhancement, signal-tonoise ratio (SNR), contrast-to-noise (CNR) and subjective image quality 6,42 (Figure 2). In a retrospective study in 2016, Yeo et al found that 6% of 403 total CTPAs were indeterminate, with 23 suboptimal examinations, and 1 non-diagnostic examination.…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 99%
“…9,36,41 There is a statistically significant negative correlation reported between mean/peak vessel enhancement and patient size. 41,42 Lowering the kVp can increase HU in the pulmonary arteries, making them appear brighter, because the attenuation of the beam increases as the beam energy reaches the k-edge of iodine. Also, less contrast can be used, and radiation dose can be reduced compared to examinations using higher kVp.…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 99%
“…Recent estimates suggest that obesity will affect more than 40% of the US population by 2030, and medical costs related to obesity in the United States were estimated at more than $140 billion in 2008 1,2 . Obesity presents problems for all medical imaging modalities but is especially problematic for computed tomography (CT), as the radiation exposure must be increased in obese patients to maintain diagnostic efficacy 3 . However, concerns about radiation dose may prevent radiologists from increasing exposure to the extent needed.…”
Section: Introductionmentioning
confidence: 99%
“…the radiation exposure must be increased in obese patients to maintain diagnostic efficacy. 3 However, concerns about radiation dose may prevent radiologists from increasing exposure to the extent needed.…”
mentioning
confidence: 99%
“…With the prevalence of obesity ever increasing, we would encourage colleagues to consider this additional dimension when caring for the bariatric patient, and not just focus on body mass in isolation. Computed tomography scanners do vary in their gantry aperture, with more modern scanners typically 75–85 cm in diameter . This information should be available from radiology staff, or alternatively a simple tape measure may be enough to prevent a wasted journey to CT.…”
mentioning
confidence: 99%